The Role of e-NOS in Chronic Cholestasis-Induced Liver and Renal Injury in Rats: The Effect of N-Acetyl Cysteine - Yusuf Gunay; Semsi Altaner; Nergiz Ekmen (Gastroenterology Research and Practice)
Introduction. The role of chronic cholestasis (CC) in liver injury and fibrosis remains unclear. The aims of this study were to define the role of endothelial nitric oxide synthase (e-NOS) in CC and the protective effect of N-acetyl-L-cysteine (NAC) in liver and kidney injury. Materials and Methods. Group A (sham group); Group B (CBDL); and Group C (CBDL + NAC). Group C received daily dosage of NAC (100 mg/kg) intraperitoneally for up to 4 weeks. Results. The rate of bridging fibrosis was higher (100% versus 20%, P=.025), but the intensity of e-NOS in liver was lower in rats that received NAC (1.3 versus 2.7, P=.046). The necrotic area in the kidneys among rats that received NAC was lower at week 4 (48% versus 57%; P<.001). The numbers of e-NOS stained cells in kidney were similar in sham group and the two groups with CBDL. Discussion. NAC reduced the stimulus for liver fibrosis in this rat model of CC and attenuated liver and kidney injury. Our study showed that e-NOS expression increased in liver tissue of rats with CC and that this was reversed by NAC. Treatment with NAC might restore e-NOS protein expression and prevent liver injury in CC.